Direct Labour as A Procurement Route for Infrastructure Delivery within Metropolitan, Municipal and District Assemblies (MMDAs) in Ghana - Osei-Asibey, Dickson (Advances in Social Sciences Research Journal, 2021)
Direct Labour procurement method has been identified as one of several procurement route alternatives used for the delivery of construction projects. This study assessed Direct Labour as a procurement route for the delivery of infrastructure within the Metropolitan, Municipal and District Assemblies (MMDAs) in Ghana. A qualitative research approach was employed using in-depth interviews conducted with ten (10) professionals who were purposively sampled from the Works Departments of the Kumasi, Accra and Tema Metropolitan Assemblies in Ghana. The qualitative data was then analysed using content analysis. Direct Labour has been revealed by this study as an effective procurement method which can be employed by the MMDAs in Ghana for the delivery of public infrastructure. The findings of the study also indicate that, the benefits of the Direct Labour procurement route include the elimination of profits to contractors and its idealness for the execution of emergency works. However, Direct Labour as a form of procurement is not used on new MMDA construction projects because the Public Procurement Act 2003 (Act 663) of Ghana as Amended in 2016, does not clearly stipulate its usage on new projects. Direct Labour procurement is used within the MMDAs mainly for maintenance works on public projects. The findings of the study would prove useful for policy re-evaluation, especially regarding the reformation of the Public Procurement Act, 2003 (Act 663) as Amended in 2016 to include Direct Labour as one of the procurement routes for the delivery of infrastructure. This would enable the MMDAs to adopt it not only for maintenance works, but also for the execution of new infrastructural projects in order to benefit from its numerous advantages.